Microbiological and Organoleptic Quality of Dried Anchovies (Stolephorus sp) in Tuntung Village - Pontoh, Syahrin; Pandey, Engel Victor; Palenewen, Joyce C. V. (Sam Ratulangi University, 2023)
Anchovy (Stolephorus sp) is a type of fish that has important economic value, besides that anchovies are widely used in various kinds of processed fishery products. The process of making dried anchovies is a product that is processed traditionally, namely by the drying process. Dried anchovies that have been processed need to be carefully packaged and stored to avoid contamination. This research aimed to identify the microbiological and organoleptic quality of dried anchovies produced in Tuntung Village, Pinogaluman District, North Bolaang Mongondow Regency. The research method used is a descriptive method with total plate number (ALT) test parameters, water content, total mold, and organoleptic (appearance, smell, taste, texture). The ALT value of dried anchovies increased during storage. The increase in ALT value was due to the processors' lack of handling of the dried anchovy products. The lowest ALT value in dried anchovies was in the 2nd processor with a storage period of 1 week of 7.9 a x 106. The highest water content was in processor 1 during the 4th week of storage with an average of 11.16% and the lowest water content was in processor A during the 1st week of storage with an average of 9.60%. The organoleptic results showed that the dried anchovy samples processed 1,2,3 met the standards up to the 2nd week of storage. The mold values showed an increase during the storage period. The highest mold value was found in the 2nd week 4 processor of 4.3 x 103 and the lowest mold value was found in the 1st week of storage of 2.0 x 103. Keywords: Anchovies, ALT, Total Mold Abstrak Ikan teri (Stolephorus sp) merupakan jenis ikan yang memiliki nilai ekonomis penting, selain itu ikan teri banyak dimanfaatkan dalam berbagai macam produk olahan perikanan. Proses pembuatan ikan teri kering merupakan salah satu produk yang diolah secara tradisioanal yaitu dengan proses pengeringan, ikan teri kering yang sudah diolah perlu dijaga pengemasan dan penyimpanan agar terhindar dari kontaminasi. Tujuan penelitian ini untuk mengindentifikasi mutu mikrobiologi dan organoleptik ikan teri kering yang di produksi di Desa Tuntung Kecamatan Pinogaluman Kabupaten Bolaang Mongondow Utara. Metode penelitian yang digunakan adalah metode deskriptif dengan parameter uji angka lempeng total (ALT), kadar air, total kapang dan organoleptik (kenampakan, bau, rasa, tekstur). Nilai ALT ikan teri kering mengalami peningkatan selama peyimpanan, terjadinya peningkatan nilai ALT disebabkan kurangnya penanganan para pengolah pada produk ikan teri kering. Nilai ALT terendah pada ikan teri kering ada pada pengolah ke 2 dengan lama penyimpanan minggu ke 1 sebesar 7,9 x 106. Kadar air ikan teri kering pada ke tiga pengolah mengalami peningkatan selama penyimpan, peningkatan kadar air pada produk disebabkan terserapnya uap air yang ada disekitar. Kadar air tertinggi ada pada pengolah 1 pada lama penyimpanan minggu ke 4 dengan rata-rata sebesar 11,16% dan kadar air terendah pada pengolah A pada lama penyimpanan minggu ke 1 dengan rata- rata sebesar 9,60%. Hasil organoleptik menunjukan sampel ikan teri kering pengolah 1,2,3 memenuhi standar sampai pada penyimpanan minggu ke 2. Nilai kapang menunjukan adanya peningkatan selama masa penyimpanan. Nilai kapang tertinggi terdapat pada pengolah 2 minggu ke 4 sebesar 4,3 x 103 dan nilai kapang terendah terdapat pada penyimpan minggu ke 1 sebesar 2,0 x 103. Kata Kunci : Ikan teri, ALT, Total Kapang